PERSEPSI GURU PAMONG TERHADAP KEMAMPUAN MERENCANAKAN DAN MENGGUNAKAN MEDIA PENGAJARAN MAHASISWA PRAKTIKUM SEKOLAH JENJANG S1 FAKULTAS DHARMA ACARYA INSTITUT HINDU DHARMA NEGERI DENPASAR DI BANGLI - Mudana, I Wayan (LPM IHDN Denpasar, 2016)
The perception of the advisor teachers towards the competence of the undergraduate students in planning and using the teaching aids during their internship period in the study year of 2014/2015, is seen to be important to study. This study describes how well is the students ability in using such aids during their internship at the schools in which they are assigned.The variables in the study include the competence in doing the plan and in using the teaching aids. The population includes 36 teachers who come from various schools, namely SDB 1 Kayubhi, SDN 3 Kayubhi, SDN 1 Cempaga, SDN 2 Cempaga, SDN 3 Cempaga, SDN 4 Cempaga who were all involved in the internship program. Since the teachers were only 36 all, the population of the study was then equal the total sampling. The study was of a descriptive kind, applied questionnaires, and percentage calculation. From the analysis, it concluded that 1) Towards planning the aids 94,45% teachers revealed positive perception and 2) Towards using the aids, 91, 67% teachers revealed positive perception.The study suggested further investigation with larger variables on the students teaching internship at schools in order to improve the quality of such program conducted by the Hindu Education Study Program of Dharma Acarya Faculty of the Denpasar State Institute of Hindu Dharma.